2016
DOI: 10.1007/s00384-016-2668-5
|View full text |Cite
|
Sign up to set email alerts
|

CONUT: a novel independent predictive score for colorectal cancer patients undergoing potentially curative resection

Abstract: CONUT score may predict survival and postoperative severe complications in CRC patients undergoing potentially curative resection. Management of CRC patients may need consideration of host nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
134
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 31 publications
5
134
3
2
Order By: Relevance
“…Postoperative major complications (CDc ≥3) were described in 7 studies [13,[16][17][18][19][20][21]. Three studies reported the CONUT score to be associated with an increased risk of major complications after esophagectomy (p = 0.034), colectomy (p < 0.001), and hepatectomy (p < 0.01) [13,16,19]. In contrast, no significant differences between groups were shown in 4 studies [17,18,20,21].…”
Section: Reported Postoperative Outcomesmentioning
confidence: 81%
See 3 more Smart Citations
“…Postoperative major complications (CDc ≥3) were described in 7 studies [13,[16][17][18][19][20][21]. Three studies reported the CONUT score to be associated with an increased risk of major complications after esophagectomy (p = 0.034), colectomy (p < 0.001), and hepatectomy (p < 0.01) [13,16,19]. In contrast, no significant differences between groups were shown in 4 studies [17,18,20,21].…”
Section: Reported Postoperative Outcomesmentioning
confidence: 81%
“…However, the other 4 studies showed no statistical differences in patients following esophagectomy, hepatectomy, and pancreatectomy [12,13,20,21]. Postoperative major complications (CDc ≥3) were described in 7 studies [13,[16][17][18][19][20][21]. Three studies reported the CONUT score to be associated with an increased risk of major complications after esophagectomy (p = 0.034), colectomy (p < 0.001), and hepatectomy (p < 0.01) [13,16,19].…”
Section: Reported Postoperative Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative malnutrition has been reported to correlate with unfavorable long-term outcomes in patients who undergo surgery for gastroenterological cancers, including esophageal (1-4), gastric (5), colorectal (6), and pancreatic (7) cancers and hepatocellular carcinoma (8). Appropriate methods are needed to preoperatively assess malnutrition likely to adversely affect long-term outcome.…”
mentioning
confidence: 99%